Cloning and expression in Escherichia coli of the naphthalene degradation genes from plasmid NAH7. - Schell, M A (1983)
The genes encoding the enzymes responsible for conversion of naphthalene to 2-hydroxymuconic acid (nahA through nahI) are contained on a 25-kilobase EcoRI fragment of an 85-kilobase NAH plasmid of Pseudomonas putida. These genes were cloned into the plasmid vectors pBR322 and RSF1010 to obtain the recombinant plasmids pKGX505 and pKGX511, respectively. To facilitate cloning and analysis, an NAH7 plasmid containing a Tn5 transposon in the salicylate hydroxylase gene (nahG) was used to derive the EcoRI fragment. The genes for naphthalene degradation were expressed at a low level in Escherichia coli strains containing the fragment on the recombinant plasmids pKGX505 or pKGX511. This was shown by the ability of whole cells to convert naphthalene to salicylic acid and by in vitro enzyme assays. The expression of at least two of these genes in E. coli appeared to be regulated by the presence of the inducer salicylic acid. In addition, high-level expression and induction appear to be mediated by an NAH plasmid promoter and a regulatory gene located on the fragment. A restriction endonuclease cleavage map of the cloned fragment was generated, and the map positions of several nah genes were determined by analysis of various subcloned DNA fragments.